(3QSGdI aj RjGOI GdYeQ hfbUGfIs - (3eQYj Hf jhSa Hf CHj HcQ Hf CMeO GdcQej GdebOSj GdMfHdi,J (B1033 (3g` s ((3Cejf Hf NjQ Gddg GdYeQi GdNWjH s)
(3ChdgG (B:s
(3GdMeO def Ndb GddhM hGdbde CeG HYO agPg aQGFO jJjeI Ydi RjGOI GdYeQ hfbUGfg hHjGf EKHGJ GdbOQ hJHjGfg ebOeI ai EKHGJ MbjbI GdbOQ s
(3BNQgG (B:s
(3hdeG cGfJ Jdc GdZSGhI efbTYI Yf CYjf GdCfHjGA Y e hHYV GdChdjGA adG MQe Cfge fXQhG Edi GdedchJ hTGgOhG YLGFHg hTGgOhG GdehJi ai YGde GdedchJ hCNHQhG Yfge hGddg SHMGfg hJYGdi CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B14s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3hbO dNU GdeDda gPg GdQSGdI ef cJGHjf dg hgeG (B:- (3HgLI GdfGXQjf (B:- (3CQhGM GdCTHGMs
(3hbO Cda gPg GdQSGdI SfI (B1033 s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3GdeLGejYs